KINERJA PERANGKAT DESA DITINJAU DARI KEPEMIMPINAN, MOTIVASI, KECERDASAN EMOSIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA PERANGKAT DESA SE KECAMATAN NGUNTORONADI KABUPATEN WONOGIRI - Muhammad Zaenal Muttaqin (JURNAL ILMIAH EDUNOMIKA, 2020)
The village government is one of the organizations in the government structure in Indonesia that has a vital role for the implementation of Government programs. So that the success of the Village Head in carrying out his organization is determined by the performance of village officials in carrying out their duties and functions. In order to improve performance in the organization, many factors influence including leadership, motivation, emotional intelligence and organizational citizenship behavior. This research took place in the village office in all Nguntoronadi District, Wonogiri Regency. Based on the calculation of the Slovin formula, the number of samples used was 88 samples. The data analysis used the t test, F test and R test. The results showed (1) there was a significant influence of leadership on the performance of village officials in Nguntoronadi District, Wonogiri Regency. (2) There is a significant influence of motivation on the performance of village officials in Nguntoronadi District, Wonogiri Regency. (3) There is a significant effect of emotional intelligence on the performance of village officials in Nguntoronadi District, Wonogiri Regency. (4) There is a significant effect of organizational citizenship behavior on the performance of Village Officials in Nguntoronadi District, Wonogiri Regency. (5) There is a significant and simultaneous influence between leadership, motivation, emotional intelligence and organizational citizenship behavior on the performance of village officials in Nguntoronadi District, Wonogiri Regency. Key Word: leadership, motivation, emotional intelligence, organizational citizenship behavior